A hemicyanine fluorescent reactive cationic dye: synthesis and applications on wool fabrics. (August 2015) - Zhang, Wei; Zhang, Yan; Cheng, Yanqiu; Qin, Chuanxiang; Chen, Guoqiang
<x xml:space="preserve">Abstract</x> A novel hemicyanine fluorescent reactive cationic dye was synthesised by the reaction between the free amino group of a hemicyanine fluorescent dye and 2, 3‐dibromopropionyl chloride. The dye was characterised by proton nuclear magnetic resonance spectroscopy, high‐resolution mass spectrometry, ultraviolet‐visible absorption spectrometry, and single‐photon fluorescence spectrometry. The prepared dye was applied to wool fabrics to give fluorescent orange shades. The colour fastness of the dyed wool fabrics was tested. Results show that dyed fabrics using the novel hemicyanine fluorescent reactive cationic dye could be used as fluorescent clothing.